Women Empowerment Through PKK-Based Family Welfare Programs: Pemberdayaan Perempuan Melalui Program Kesejahteraan Keluarga Berbasis PKK - Mauludia, Mivtha; Agustina, Isna Fitria (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Women play a central role in family welfare and community development, yet gender inequality still limits their economic and social participation. Specific Background: The PKK (Family Welfare Empowerment) program serves as a national grassroots initiative for women’s empowerment through education, skills training, and entrepreneurship. Knowledge Gap: Despite many studies on PKK, limited research focuses on its implementation in rural Sidoarjo context and its outcomes on women’s socio-economic capacity. Aims: This study aims to analyze how PKK contributes to women’s empowerment through local community activities and training programs. Results: The findings show that PKK successfully increases women’s knowledge, creativity, and household economic independence through community-based training such as handicrafts and home industries. However, program sustainability is constrained by limited funding, facilities, and management. Novelty: The study identifies PKK as a transformative local governance model integrating education, entrepreneurship, and gender awareness. Implications: Strengthening managerial capacity, continuous training, and digital marketing access are essential to sustain women’s empowerment through PKK programs. Highlights: PKK enhances women’s skills and self-reliance. Local initiatives strengthen family and community welfare. Sustainability needs better resource management.